WATER AS AN ELECTROLYTE TO LIFE (Wudil Journal of Science and Technology Education, 2025)
Water is universally recognized as the foundation of life, playing roles that go far beyondhydration. It acts as a solvent, transport medium, temperature regulator, and the carrier ofelectrolytes that sustain nearly all biological processes. Electrolytes such as sodium, potassium,calcium, magnesium, chloride, bicarbonate, and phosphate are critical for nerve transmission,muscle contraction, acid-base regulation, and cellular homeostasis. This paper explores theessential role of water as an electrolyte solvent to life, emphasizing its physiological importance,storage in the body, interaction with electrolytes, balance across compartments, and the dietarysources that naturally replenish electrolytes. By taking a health-oriented approach, the paperunderscores how everyday hydration and nutrition practices can maintain optimal electrolytebalance and prevent common health challenges such as dehydration, fatigue, and muscledysfunction. Therefore, it was recommended that specific actions be taken to promote hydrationand electrolyte health across all sectors, including individual, clinical, and policy domains.
Keywords: Electrolytes, Cellular Homeostasis, Hydration and Nutrition